1992
DOI: 10.3168/jds.s0022-0302(92)77743-1
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Intensively Managed Rotational Grazing, Traditional Continuous Grazing, and Confinement Housing on Bulk Tank Milk Quality and Udder Health

Abstract: Monthly bulk tank milk samples and veterinary records were analyzed for 1 yr on 15 Vermont dairy farms. Data were evaluated using ANOVA to compare effects of grazing management systems on milk quality and udder health. Systems evaluated were intensively managed rotational grazing, traditional continuous grazing, and confinement housing. Bulk tank samples were evaluated for standard plate count, bacterial type counts on tryptose-blood-esculin agar, and SCC. Veterinary records were evaluated for incidence of cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
47
1
2

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 10 publications
4
47
1
2
Order By: Relevance
“…The stay of dairy cows in pasture markedly contributes to the higher cleanness of dairy cows and their udders, and naturally to the lower microbial contamination of milk. Lower values of TBC in pasture management of dairy cows were also reported by McKinnon et al (1990), Goldberg et al (1992) and Regula et al (2002). Our results document that besides the reduction in TBC in pasture management the contamination of milk by psychrotrophic bacteria and technologically risky proteolytic and lipolytic bacteria also decreases.…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…The stay of dairy cows in pasture markedly contributes to the higher cleanness of dairy cows and their udders, and naturally to the lower microbial contamination of milk. Lower values of TBC in pasture management of dairy cows were also reported by McKinnon et al (1990), Goldberg et al (1992) and Regula et al (2002). Our results document that besides the reduction in TBC in pasture management the contamination of milk by psychrotrophic bacteria and technologically risky proteolytic and lipolytic bacteria also decreases.…”
Section: Resultsmentioning
confidence: 51%
“…McKinnon et al (1990) reported that housed dairy cows with obviously clean udders might contribute to contamination by more than 10 000 CFU/ml of milk while grazing dairy cows with clean teats might contribute less than 100 CFU/ml of milk. Lower values of TBC in grazing management systems in dairy cows were also reported by Goldberg et al (1992) and Regula et al (2002).…”
mentioning
confidence: 54%
“…Housing conditions (bedding material, litter management) and milk house water supply can also influence the quality of the milk (27,29,43). Moreover, according to the maintenance and the microbial diversity of milk, biofilms formed in the milking machine can inoculate the milk (9).…”
mentioning
confidence: 99%
“…Herd size has been reported to have a positive correlation with total aerobic count and CC probably due to confinement and greater contamination (Elmoslemany et al, 2010;Goldberg et al, 1992). In the study of Jayarao et al (2004) herd size did not affect the SPC, PIC and LPC but affected the CC.…”
Section: The Effect Of Herd Sizementioning
confidence: 66%